(untitled) (Pulse, 2014)
Large left to right shunt across an atrial septal defect results in volume overload and dilatation of the right atrium and ventricle. As a result of increased flow into the lungs, the pulmonary arteries, capillaries & the veins are dilated & there can be flow related pulmonary artery hypertension. Overtime this can lead to medial hypertrophy of pulmonary arteries & muscularization of arterioles resulting in pulmonary vascular obstructive disease. Once PAH develops, it is challenging to determine operability and predict outcomes after repair in borderline situations. We report a woman with large atrial septal defect and severe pulmonary hypertension 9.84 wood units /m2 of indexed total pulmonary vascular resistance. She underwent successful corrective repair of atrial septal defect after 4 months of medical management. This case supports that careful evaluation of reversibility of borderline pulmonary arterial hypertension associated with atrial septal defect and pre operative medical management with advanced pulmonary vasodilator therapy can modify a life to normal following closure of ASD. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20349 Pulse Vol.6 January-December 2013 p.44-47